Gender and business owner satisfaction: The case of farm and non-farm family businesses in the Midwest. Issue 4 (29th November 2019) - Li, Wenxuan; Marshall, Maria I.
Abstract : Purpose: The purpose of this paper is to investigate how the factors associated with role satisfaction in farm and non-farm family businesses differ by gender of the business owner. Design/methodology/approach: The data used are from a 30-minute telephone survey of owners of farm and non-farm family businesses in Indiana, Illinois, Michigan and Ohio. The sample consists of 627 small- and medium-size family businesses. Three ordered probit regressions are used to analyze role satisfaction. Findings: Women's participation in management and the number of family members in management are positively associated with women's role satisfaction, while tension from resource competition is negatively associated with role satisfaction. In contrast, men's role satisfaction is increased through high family business functioning and profit. Practical implications: There is no difference in the level of role satisfaction between men and women when one controls for the owner, family and business characteristics. However, there is a difference in the factors that drive role satisfaction between men and women. This may be driven, in part, by what their roles are vis-à-vis the financial aspects of the business. Male and female business owners seem to focus on different aspects of their family business to achieve role satisfaction. Originality/value: This paper determines the impact of gender on the role satisfaction of business owners of farm and non-farm family businesses in four Midwestern states. It identifies the different factors associated with role satisfaction for female and male family business owners based on their actual roles.